Experimenting with Farmers’ Capacity and Social Institutions Building for ensuring Village Level Seed Sufficiency: A Case of Chickpea (Cicer arietinum L) in India (Indian Journal of Extension Education, 2015)
Building farmers’ capacity to experiment with the recommended technologies and at the same time facilitating them for institutionalizing their efforts requires constant validation, consolidation and upscaling. An action research was conducted to empirically probe how the recommended and improved seed varieties may appear if looked with farmers’ lens and how to a large extent the farmers’ preferred varieties may reach, while using the interventions of institutional backstopping, capacity building, hand holding and enabling. Chickpea is a major pulse crop of India. However, its productivity is restricted around 896 kg/ha, over the past several decades. Local landraces and varietal admixture are influencing the chickpea cultivation in the country. One of the major reasons for low productivity of chickpea is the non availability of quality seed of improved varieties among the farmers. In the present paper, the experiences of farmer participatory chickpea seed production in districts of Fatehpur and Kanpur Dehat in Uttar Pradesh state of India have been shared. Through farmer-participatory varietal selection trials, farmers identified DCP 92-3 and JG 16 varieties, as their preferred choices. These varieties were preferred because of its high yield, attractive seed size, seed color, better taste and cooking quality. Farmers were organized to form cooperative societies to undertake seed production, processing and marketing at the local level. They were also linked with the public sector seed producing agencies to participate in the formal seed production program. The B:C ratio of seed production of DCP 92-3 and JG 16 variety was 2.94 and 3.18 as compared to 2.15 of the local chickpea variety sold as grain. Village level seed production not only addressed the issue of shortage of quality seeds but also brought higher incomes to farmers leading to their improved livelihood.